2023
DOI: 10.3390/ijms242115831
|View full text |Cite
|
Sign up to set email alerts
|

Switching Rat Resident Macrophages from M1 to M2 Phenotype by Iba1 Silencing Has Analgesic Effects in SNL-Induced Neuropathic Pain

Roxana-Olimpia Gheorghe,
Andreea Violeta Grosu,
Melania Magercu
et al.

Abstract: Resident macrophages from dorsal root ganglia are important for the development of traumatic-induced neuropathic pain. In the first 5–7 days after a traumatic sciatic nerve injury (i.e., spinal nerve ligation (SNL), spared nerve injury (SNI), sciatic nerve transection or sciatic nerve ligation and transection), Ionized binding adapter protein 1 (Iba1) (+) resident macrophages cluster around dorsal root ganglia neurons, possibly contributing to nerve injury-induced hypersensitivity. Since infiltrating macrophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 108 publications
0
2
0
Order By: Relevance
“…AIF1 is known to induce the production of pro-inflammatory molecules, including the inflammatory factors IL-6 and TNF-α, and cause elevation of reactive oxygen species (ROS) ( 50 ). Furthermore, it has been shown that the role of AIF1 in macrophages is critical for maintaining their survival and promoting inflammatory activity ( 51 , 52 ). Based on these properties, it is reasonable to assume that there may be a positive correlation between AIF1 and AS, which is an immune-mediated disease characterized by chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…AIF1 is known to induce the production of pro-inflammatory molecules, including the inflammatory factors IL-6 and TNF-α, and cause elevation of reactive oxygen species (ROS) ( 50 ). Furthermore, it has been shown that the role of AIF1 in macrophages is critical for maintaining their survival and promoting inflammatory activity ( 51 , 52 ). Based on these properties, it is reasonable to assume that there may be a positive correlation between AIF1 and AS, which is an immune-mediated disease characterized by chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, upregulation of BDNF in mast cells was observed following back pain associated with intervertebral disk degeneration [210] and intradiscal inflammatory stimulation induces spinal pain behavior and intervertebral disc degeneration in vivo with an increase of macrophage markers and BDNF (as well as other nociceptive markers) [211]. Furthermore, studies have shown that following various forms of severe sciatic nerve damage, resident macrophages expressing Iba1 protein gather around DRG neurons, thereby exacerbating pain hypersensitivity caused by nerve injury [212]. This study also found that by inhibiting the expression of Iba1 and modifying the characteristics of resident macrophages, specifically shifting them from an M1 to an M2 phenotype, analgesic effects can be achieved in neuropathic pain caused by SNL.…”
Section: Immune Cellsmentioning
confidence: 99%